2020
DOI: 10.36390/telos221.07
|View full text |Cite
|
Sign up to set email alerts
|

Estrés Académico y Trabajo de Grado en Licenciatura en Educación

Abstract: La investigación tuvo por objetivo determinar el impacto del estrés académico durante el proceso de realización del trabajo especial de grado en estudiantes de Licenciatura en Educación. El estrés académico fue sustentado teóricamente desde la vertiente de autores como: Berrío y Mazo (2011), Castillo Pimienta et al. (2016), Méndez y Gálvez (2018), Moran et al. (2018).  Metodológicamente se trabajó con una investigación correlacional. La muestra de estudio, estuvo conformada por 167 estudiantes. La correlación … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
2
1
0
1
Order By: Relevance
“…This result is aligned to what Herrero et al (2019) mentioned, who concluded that the management of these parameters allowed to materialize the learning objectives in the studied population. Similarly, the results obtained were close to those of Quiliano and Quiliano (2020) as well as those of Aldana, Isea, and Colina (2020), who demonstrated that stress kept a close inverse association with parameters related to time management in academic life.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This result is aligned to what Herrero et al (2019) mentioned, who concluded that the management of these parameters allowed to materialize the learning objectives in the studied population. Similarly, the results obtained were close to those of Quiliano and Quiliano (2020) as well as those of Aldana, Isea, and Colina (2020), who demonstrated that stress kept a close inverse association with parameters related to time management in academic life.…”
Section: Discussionsupporting
confidence: 82%
“…Previous research on stress associated with emotional intelligence using the Bar-On and SISCO inventories revealed there is a strong association between both variables in populations of young health science students (Quiliano and Quiliano, 2020). Similar results were obtained by Aldana et al (2020) in measuring stress when students earn their degree. Other studies on Medicine students by means of the SISCO test demonstrated the existence of significant levels of stress when they are submitted to examinations (stressors), generating an impact on the quality of sleep as well as anxiety conditions (Otero, Carriazo, Oliver, Lacayo, Torres and Pá jaro, 2020).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…A partir de los resultados obtenidos, se concuerda con lo planteado por (Aldana et al 2020), donde se indica que el estrés puede producirse por la acumulación de una serie de responsabilidades educativas, visión respalda por (Molek-Winiarska & Kawka, 2022), siendo necesario generar un proceso de autorregulación como medida para contrarrestar tal situación, esta medida se representa en las habilidades blandas, propuesta respaldada por (Rabaglietti, et al 2021, Donna, 2020.…”
Section: Discussionunclassified